A inclusão de crianças com necessidades educacionais especiais na educação infantil: uma análise do currículo moldado pelas práticas pedagógicas de professoras da rede municipal de ensino de Belém - AMARAL, Míriam Matos (2006)
The research makes an analysis of moulded curriculum by pedagogical practices developed by teachers from Belém-Pará municipal net begining from education inclusion in the pre-school of kids with special education necessities (NEES) proposed in Cabana School pedagogical politic project. So, our issue-questions, to point aiming to investigate as if gave the education inclusion of kids with Special Education Necessities after the introdution of Cabana School Project; wich pedagogical practices were adopted by teachers that attended kids with NEES included in preschools of teach net of Belém municipal district begining of "People's Government" (1997-2004) and yet, wich curriculum was moulded begining of pedagogical practices of teachers after inclusion. We have as objectives of research, to analysis the education inclusion process in net, to identify the pedagogical practices adopted by teachers and analysis the curriculum that were moulded after the inclusion in the Infantile Education of kids with NEES. In the realization of study adopted a qualitative approach, making use of semi structured interviews and document analysis in process of data collect. The results of research reveal that the process of educational inclusion executed in the schools and unitys of Infantile Education of municipal net if gave with big structural difficulty, mainly in the introdution of adaptations in access in the curriculum of Infantile Education. For the teachers, the kids inclusion with NEES was a big challenge in your pedagogical practices. The access in the school knowledge for this kids if gave, so, with the moulded curriculum by practices of teachers thah experienced the education inclusion movement in Cabana School.